The Shadow Banking System - Survey and Typological Framework - Jenny Poschmann (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2012)
Even though the sector of Non-bank financial intermediaries (NBFI) or shadow banks represent a large part of the contemporary financial system, these institutions received almost no attention in macroeconomic studies so far. Their presence has significant influence on the conduct of monetary policy and systemic risk within the financial system. Therefore, it is important to understand the nexus within the shadow banking sector and connections with the traditional banking sector. This work will examine specific institutions involved in the shadow banking system and their development. A stylized banking sector including NBFI will be introduced and provides the starting point for subsequent research on monetary transmission.
urn:nbn:de:gbv:27-20131119-145608-9
Keywords: G10; E44; 330; shadow banking; financial intermediation; financial architecture; monetary policy; Finanzintermediation; Investmentbank; Finanzsektor; Geldpolitik; Geldpolitische Transmission; Systemrisiko; Makroökonomischer Einfluss; Theorie; Welt